Towards A Rare Disease Registry Standard: Semantic Mapping of Common Data Elements Between FAIRVASC and the European Joint Programme for Rare Disease - Yaman, Beyza; Hederman, Lucy; O'Sullivan, Declan; Little, Mark; McGlinn, Kris (My University, 2022)
This paper describes the extension of the FAIRVASC rare disease ontology, with Joint Research Council Common Data Elements (CDE), and mapping to the European Joint Programme on Rare Dis- eases (EJP RD) CDE ontology. We use the rare autoimmune condition ANCA vasculitis as a model disease to illustrate this. Semantic modelling of CDE for Rare Diseases over registry data is important to represent the specific concepts around these conditions. We describe the develop- ment of an ontology which facilitates the simultaneous uplift of tabular data into a common RDF format from several registries. The ontology allows the data to be integrated across the registries and increases the interoperability and standardisation among datasets, thus enhancing col- laboration with external stakeholders. The ontology, therefore, creates an effective rare disease research environment which enables the disease and its impact on the patient to be investigated in an effective manner across national borders. This paper presents the methodology and road map to implement the CDE ontology for the health domain.
5th Workshop on Semantic Web solutions for large-scale biomedical data analytics (SeWeBMeDA-2022)
Keywords: Ontology; Health informatics; Rare disease; Digital Engagement; Health informatics; ontology; rare diseases; Other; Health